How do women feel about their cervical cytology samples being used for research?. Issue 1 (16th August 2011) - Coope, Caroline; Rose, Karen; Glasier, Anna; Stephenson, Judith
Abstract : Background and methodology: The introduction of liquid-based cytology (LBC) for cervical screening in the UK has enabled research into human papillomavirus as an adjunct to screening and provides potential opportunities for population-based research into women's health. The authors explored women's views on the use of remnant LBC samples for sexual and reproductive health research. A pilot study was conducted to assess the acceptability of collecting and storing remnant LBC specimens for future use in sexual and reproductive health research. Women attending a clinic for their routine smear test were recruited to the study. Semi-structured interviews were conducted with a subsample of the women to explore acceptability issues. Results: Of women invited to participate ( n =369), 86% ( n =316) consented to the storage and use of their remnant sample for research. Of these, 96% ( n =304) consented to their sample being linked to reproductive health records. Women interviewed ( n =23) were happy with the research process although unclear about what future research might be conducted on their specimen and what health records would be accessed. Discussion and conclusion: As research becomes technically and ethically more complex the challenge remains to find the right balance between providing sufficient relevant information to ensure informed consent and allay participant's fears, while guarding against the inclusion of excessive detail. The introduction of LBC for cervical screening across the UK brings a new opportunity to integrate research studies within a national cervical screening programme. Our study suggests this is acceptable to women.